Influence of spray-drying process on properties of chitosan/xanthan gum polyelectrolyte complexes as carriers for oral delivery of ibuprofen - Ćirić, Ana; Milinković Budinčić, Jelena; Medarević, Đorđe; Dobričić, Vladimir; Rmandić, Milena; Barudžija, Tanja; Malenović, Anđelija; Petrović, Lidija; Đekić, Ljiljana (Archives of Pharmacy, 2022)
Polyelectrolyte complexes (PECs) are attractive carriers with recognized potential to enhance oral delivery of poorly soluble high-dosed low-molecular-weight drugs. The formulation of solid oral dosage forms requires the drying of PECs, which may affect their physicochemical and biopharmaceutical properties. The aim of this study was to investigate the effect of spray-drying on the properties of ibuprofen-loaded chitosan/xanthan gum PECs and to assess the drug release kinetics from such PECs filled into hard capsules in comparison with corresponding PECs which are dried under ambient conditions. The yield, ibuprofen content, entrapment efficiency, and residual moisture content of spray-dried PECs were lower than those of ambient-dried PECs. Better flowability of spray-dried PECs was attributed to the almost spherical particle shape, shown by scanning electron microscopy. DSC and PXRD analysis confirmed the amorphization of ibuprofen during spray-drying. All the investigated PECs, obtained by drying under ambient conditions as well as by spray-drying, had high rehydration capacity both in 0.1 M hydrochloric acid (pH 1.2) and phosphate buffer pH 7.4. In vitro ibuprofen release from dried PECs was controlled during 12 h with the release of approximately 30% of entrapped ibuprofen. Spray-dried PECs provided better control of ibuprofen diffusion from the carrier compared to the ambient-dried ones.
Keywords: chitosan; xanthan gum; ibuprofen; spray-drying; controlled drug release